A Soluble Donor-Acceptor Double-Cable Polymer: Polythiophene with Pendant Fullerenes - Cravino, Antonio; Zerza, Gerald; Maggini, Michele; Bucella, Stefania; Svensson, Mattias; Andersson, Mats R.; Neugebauer, Helmut; Brabec, Christoph; Sariciftci, Niyazi Serdar (Monatshefte für Chemie, 2003)
We report the synthesis and the spectroscopic properties of a novel soluble thiophene-based copolymer carrying pendant fullerene moieties (donor-acceptor double-cable polymer). Photoinduced absorption (PIA) experiments on spin cast films reveal a photoinduced electron transfer from the polythiophene chain onto the fullerene moieties. The performance of photovoltaic devices produced with this copolymer is also discussed.
Keywords: Double-cable polymers; Fullerenes; Organic photovoltaics; Photoinduced spectroscopy; Polythiophenes